Double standards and their impact on world peace (Salam International Academic Journal, 2011)
The research explains that a just international system is considered a legitimate requirement and a necessity for achieving peace and stability. However, the contemporary reality of international institutions and their adoption of double policies has made the international system threatened and caused these institutions to lose credibility, leading to the spread of the use of force instead of peaceful solutions.   The research begins by clarifying the concept of "double policy," meaning the contradictory behavior of international institutions toward similar issues, as seen in the United Nations’ treatment of Iraq and Sudan compared to Israel.It then highlights the main causes of this duality, including:1.      The colonial goals of major powers seeking to protect their interests in the Third World.2.      Religious objectives, especially the influence of Christian Zionist groups on Western policies toward Israel.After that, it presents the Islamic principles on which a just international system is based, such as:Justice and equality in international relations.Fulfilling promises and adhering to agreements.Cooperation in goodness and refraining from cooperation in oppression.The study then discusses examples of the United Nations’ double policies, such as the Palestinian issue, where dozens of resolutions against Israel were not implemented, while strict measures were taken against Sudan, as well as in cases involving prisoners and wars in Iraq and Afghanistan.The research concludes that such duality has led to a loss of trust in international institutions and has threatened global peace, as it has pushed nations to adopt the logic of force instead of dialogue, weakened peaceful reform movements, and increased internal conflicts in Islamic countries.Finally, the researcher, citing the opinions of several Muslim leaders and thinkers, affirms that double policies are the root of many of today’s global crises and that the solution lies in returning to justice and both human and Islamic principles in managing international relations.
Keywords: Double standards; global peace; the United Nations; international relations